Hubungan Gaji Guru Dengan Kesejahteraan Hidup Guru Sekolah Negeri Dan Swasta - Aulia Febriyanti; Melisa Safitri; Dewi Purnama Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the relationship between teacher salaries and the level of teacher well-being in public and private schools. Using a descriptive qualitative approach, data were collected through questionnaires distributed to 50 teacher respondents from various educational backgrounds and institutions. The results indicate that salary influences teachers' perceptions of well-being, particularly in terms of meeting basic needs, emotional stability, and work motivation. However, it was also found that well-being is not solely determined by salary, but also by other factors such as the work environment, workload, and opportunities for self-development. These findings provide an important contribution to education policymakers in designing a more equitable reward system oriented towards improving the quality of life of educators.